Analysis of Promotions, Price Perceptions, and Product Quality on Purchasing Decisions (Marketing Management Literature Review) - Silviah, Reni (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
Literature Review of the influence of Promotion, Price Perception, Product Quality, on Purchasing Decisions is a scientific article used to build research hypotheses on the influence between variables that will be used in further research. The method of writing a literature review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other online media. The results of this article 1) Promotion influences Purchasing Decisions; 2) Price Perception influences Purchasing Decisions; 3)Product Quality influences Purchasing Decisions. Apart from these 3 exogenous variables that influence the endogenous variable of Purchasing Decisions, there are still many other factors including consumer reviews, trust, brand image.